PENGARUH METODE CAMPBELL DUDECK SMITH DALAM PENJADWALAN PRODUKSI TABLE 76-0001-VENEER MESIN SHOP PT.CEGEONE - Spalanzani, Widya (Jurnal Jaring SainTek, 2021)
CEGEONE (CG) is a manufacturing industry company in furniture. It is a supplier company for the Horrison & Gil company. The company manufactures furniture from raw materials into semi-finished goods. The company produces its products on consumer demand (customized order). The overwhelming and varying amount of demand each period was a major problem in the company's production. Hence it takes scheduling. Production scheduling is an important process in production system. In the production process, particularly in the Shop Machine line there is often bottle neck. Under that, researchers did production scheduling at the Shop Machine with the Campbell Dudeck Smith (CDS) method. This method uses Johnson's algorithm that aims to determine the order of the job in order for the earned makespan to be smaller than before. Using production scheduling on shop machines, the company can reduce the total process time to complete the job by 95 minutes or 1 hour 35 minutes. Smaller compared to the previous total makespan of 250 minutes or 4 hours 10 minutes. So that shows total savings in production at 19.79%. The results of the study can be concluded that by using production scheduling on shop machines.